فقہ الاقلیات المسلمۃ و اھمیتہ فی العصر الجدید(تاصیلاً و تطبیقاً): The Jurisprudence of Muslim Minorities and Its Importance in the Modern Era (Theoretical Foundation and Application) - Akbar, Dr. Hafiz Muhammad; Dr Manzoor Ahmad, Dr Manzoor Ahmad; Abdullah, Hafiz Muhammad (Al-Amīr Research Journal for Islamic Studies, 2023)
This article emphasizes the critical importance of Fiqh al-Aqalliyyat, or Jurisprudence for Muslim Minorities, in today’s global context. It outlines how this branch of Islamic jurisprudence offers practical guidance to Muslims living as minorities in non-Islamic societies, aiding them in maintaining their religious practices and identity. Fiqh al-Aqalliyyat addresses the challenges these communities face, including the need for peaceful coexistence and the opportunity to correct misconceptions about Islam in the West. The article underscores the dual role of Fiqh al-Aqalliyyat: preserving the religious life of Muslim minorities while promoting a positive image of Islam. It advocates for a modernized approach to Islamic jurisprudence that considers the unique situations of Muslims living outside predominantly Islamic countries. This includes developing new legal opinions that are relevant to contemporary issues, ensuring that Islamic teachings remain applicable and accessible. In summary, Fiqh al-Aqalliyyat is portrayed as an essential tool for Muslim minorities, facilitating their integration into diverse societies without compromising their faith. It highlights the necessity for continual jurisprudential evolution to foster understanding and harmony between Muslims and the broader community. Keywords: Fiqh-ul-Aqalliyyat, Religious life, Islamic jurisprudence, Peaceful coexistence, Western societies.